2015
DOI: 10.1676/13-200.1
|View full text |Cite
|
Sign up to set email alerts
|

Habitat use and nesting success of the Great Reed Warbler (Acrocephalus arundinaceus) in different reed habitats in Serbia

Abstract: ABSTRACT.---We surveyed five reed habitats (mining pond, sand pit, large canal, small 1 canal and lowland river) in north-western Vojvodina (Serbia) between 2009-2011 to study 2 habitat use and to estimate nest success in an understudied region of the breeding range of the 3 Great Reed Warbler (Acrocephalus arundinaceus). Data from 174 nests showed that habitat 4 use differed considerably between the habitat types, but was not related to the area of the 5 study site or the reed bed. Higher-than-expected number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
(30 reference statements)
1
18
0
Order By: Relevance
“…two per nest) were similar as in the short-term study of . Furthermore, previous studies confirm similar clutch sizes, number of fledglings and nesting success (ranging from 23.1% to 59.7%) in the Great Reed Warbler in various reed habitats in Central Europe (Beier 1981, Dyrcz 1981, Petro et al 1998, Mérő et al 2015b. found that nesting success was similar in both burnt and non-burnt reed patches.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…two per nest) were similar as in the short-term study of . Furthermore, previous studies confirm similar clutch sizes, number of fledglings and nesting success (ranging from 23.1% to 59.7%) in the Great Reed Warbler in various reed habitats in Central Europe (Beier 1981, Dyrcz 1981, Petro et al 1998, Mérő et al 2015b. found that nesting success was similar in both burnt and non-burnt reed patches.…”
Section: Discussionmentioning
confidence: 52%
“…In this study, we define the nesting success as the probability that an egg produces a fledgling. The multiplication of the egg and nestling survival rate for the entire incubation and nestling period and the hatching rate resulted in the final nesting success rate, and was then converted to percentages (Mérő et al 2015b). In this study, the hatching rate is defined as the probability that an egg present at hatching time produces a hatchling (Mayfield 1975).…”
Section: Methodsmentioning
confidence: 99%
“…The great reed warbler is a typical ‘edge-species’ which prefers to breed on the edge of the reed beds and in the narrow reed-stripes found alongside irrigation channels 47,48 . These high-quality habitats, despite being quickly occupied by early-arriving, large-winged and presumably higher-quality males, are characterized by higher rates of brood parasitism 4951 . Therefore, irrigation channels function as ecological traps 50,51 and habitats for sink populations, dependent on the influx of naïve individuals from the habitats with low parasitism rates 52 .…”
Section: Discussionmentioning
confidence: 99%
“…However, they are also very easily flooded by rising tides that can overturn nests (Martijn et al 2010). In addition, reproductive costs may be much larger when a previously suitable habitat experiences a sudden change (like a flood or hurricane) (Mérő et al 2015).…”
Section: Discussionmentioning
confidence: 99%